ENDOTHELIAL GLYCOCALYX DEGRADATION IN CEREBRAL EDEMA: PROMISING OPPORTUNITIES FOR INTENSIVE CARE - V.V. MASSOROV; YU.V. BYKOV; V.A. BATURIN; A.P. VOROBYOVA (Паёми Сино, 2025)
A literature review was conducted on the role of the endothelial glycocalyx (eGC) in the pathogenesis of cerebral edema (CE) and the management methods within the context of intensive care. The search for relevant information was carried out using the PubMed, ScienceDirect, and eLibrary databases, employing the following keywords: "cerebral edema", "glycocalyx", "methods of drug correction", "pathogenesis", and "intensive care". The inclusion criteria for thisreview were studiesthat explored markers of eGC degradation in CE and investigationsinto the effects of various methods